(untitled) (Fiep Bulletin - online, 2012)
Goal is a strategy used by motor learning, in order to enable the educator or learner to direct their focus of attention inquantitative or qualitative performance in a specific unit of time, besides being a motivational strategy, attribute is also acontributor to maximize the performance improvement. Thus, it is likely that when the student self-establish a goal to beovercome, or when the teacher set a goal to the student, it strives for more success. With the assumptions presented, theobjective work was to verify setting targets had some effect on the performance of adolescents. For that, was conducted a trainingprogram of jogging and jumping, with 12 adolescents with about 14 years old, which were divided into two groups. One with atarget evaluated without GOM, while the other was evaluated with the goal of “overcome its best” GSM. The results did not detectdifferences between the groups with or without goals. At the end of the experiment, a questionary was applied on both groups toanalise self establishment of goals and the results indicated that the one of GSM, 66,6% had self established goals during theexperiment. This can indicate that the results may have been influenced by the self-established strategy made by the teenagers.